2014
DOI: 10.15288/jsad.2014.75.635
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Mediates the Relationship Between ADH1B and DSM-IV Alcohol Use Disorder and Criteria

Abstract: ABSTRACT. Objective: A single nucleotide variation in the alcohol dehydrogenase 1B (ADH1B) gene, rs1229984, produces an ADH1B enzyme with faster acetaldehyde production. This protective variant is associated with lower alcohol consumption and lower risk for alcohol use disorders (AUDs). Based on the premise that faster ADH1B kinetics decreases alcohol consumption, we formally tested if the association between ADH1B variant rs1229984 and AUDs occurs through consumption. We also tested whether the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…49 Across these studies, the most robust association signal for rs1229984 appears to arise from Tolerance, which is notably an index of excessive consumption and consistent with the role of ADH1B in other studies of nonproblem alcohol intake. However, another study of 1130 individuals of Jewish descent reported associations between rs1229984 and both Tolerance and Desire to cut drinking.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…49 Across these studies, the most robust association signal for rs1229984 appears to arise from Tolerance, which is notably an index of excessive consumption and consistent with the role of ADH1B in other studies of nonproblem alcohol intake. However, another study of 1130 individuals of Jewish descent reported associations between rs1229984 and both Tolerance and Desire to cut drinking.…”
Section: Discussionsupporting
confidence: 71%
“…However, another study of 1130 individuals of Jewish descent reported associations between rs1229984 and both Tolerance and Desire to cut drinking. 49 Across these studies, the most robust association signal for rs1229984 appears to arise from Tolerance, which is notably an index of excessive consumption and consistent with the role of ADH1B in other studies of nonproblem alcohol intake. 50 Plausibly, the strong findings with Desire to cut drinking might also support this as epidemiological studies have shown this criterion to index liability to less severe AD (Table S2 and Figure S7), and therefore, serve as a marker of excessive drinking, rather than severe pathology and impairment.…”
Section: Discussionsupporting
confidence: 71%
“…A recently published article examined the relationship between rs1229984 and individual DSM‐IV AUD criteria in an Israeli population‐based sample (Kilcoyne et al . ). The authors found that tolerance, repeated attempts to quit, used larger amounts longer, physical/psychological problems, hazardous use and social problems were significantly associated with ADH1B .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, data used to guide the DSM-5 diagnostic thresholds and severity cut points were based largely on current disorders (Hasin et al, 2013). Although current disorders are less likely to be prone to recall biases (Grant et al, 2004), lifetime diagnoses are also relevant in contexts including identification of indications and contraindications for specific treatments, assessing risk and targeting prevention for chronologically secondary disorders , and phenotypic classifications for genetic studies (e.g., Bi et al, 2014;Kilcoyne et al, 2014). Furthermore, although the DSM-IV abuse diagnosis required only one criterion to be positive, the DSM-5 threshold of 2+ criteria has been criticized as too low on the grounds that large numbers of individuals manifesting very mild symptomatology will be diagnosed (e.g., Martin et al, 2011;Mewton et al, 2011Mewton et al, , 2013.…”
Section: Aims Of the Present Studymentioning
confidence: 99%